THE IMPACT OF INVESTMENT DECISIONS AND FINANCING DECISIONS ON FIRM VALUE WITH FIRM SIZE AS A MODERATING VARIABLE (In Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange for 2022-2024) - Adinda Ayu Puspitasari; Aminatuzzuhro Aminatuzzuhro; Andi Iswoyo (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2026)
This study aims to examine the effect of investment decisions and financing decisions on firm value with firm size as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange during the 2022-2024 period. The study employed a quantitative approach using purposive sampling, resulting in 26 sample companies. The data were analyzed using panel data with Eviews 13. The results indicate that investment decisions have no significant effect on firm value, while financing decisions have a positive and significant effect on firm value. Furthermore, firm size does not moderate the relationship between investmen decisions and firm value but moderate the relationship between financing decisions and firm value.